Príručka súdneho lekárstva - Kokavec, Milan, sr., 1927-2004; Porubský, Vladimír, 1921-2017; Mego, Mirko, 1928-; Korman, Vladimír; Bauer, Miroslav, 1930-2018 (Učebnice pre lekárske fakulty, 1972)
Resumé rusky, anglicky a nemecky